Sustainable Layout Design Based on Integrated Systematic Layout Planning and TOPSIS: A Case Study - Meiliza Dresanala; Shanty Kusuma Dewi; Dana Marsetiya Utama (Jurnal Teknik Industri, 2023)
This research applies the concept of sustainable layout in the manufacturing industry by incorporating social, environmental, and economic aspects in the production process. The main objective of this research is to design a sustainable layout for the plastic packaging manufacturing industry. The approach utilizes the TOPSIS method to select an Activity Relation Chart (ARC) integrated with a systematic Layout Planning procedure. A case study is presented on an industry that produces plastic packaging in Indonesia. The results show that the proposed sustainable layout design significantly reduces the material handling distance compared to the initial layout. These results confirm that the Systematic Layout Planning approach and TOPSIS method have great potential in designing layouts that integrate sustainable principles effectively in manufacturing environments.